Tokyo ghoul:re. 6 - Ishida, Sui (Viz signature., 2018)
The Commission of Counter Ghoul is the only organization fighting the Ghoul menace, and they will use every tool at their disposal to protect humanity from its ultimate predator. Their newest weapon in this hidden war is an experimental procedure that implants human investigators with a Ghoul<U+2019>s Kagune, giving them Ghoul powers and abilities. But both the procedure and the newly formed Qs Squad are untested. Will they become heroes<U+2026>or monsters?! The CCG never thought that taking down the Rosewald family would be easy and, as expected, the casualties are piling up. Numbered among the wounded is Haise Sasaki, whose critical injuries leave him vulnerable when the past threatens to overwhelm him!